PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI KARTUN DI SEKOLAH DASAR - Anisa Lusiana Komara; Aan Subhan Pamungkas; Ratna Sari Dewi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes the development of cartoon animation video-based learning media in elementary schools, the feasibility of cartoon animation video-based learning media in elementary schools, and the student responses to cartoon animation video-based learning media in elementary schools. The study described in this article used Research and Development (R&D) by using a 4D model with the stages, namely define, design, development, and dissemination. The data collection techniques used were interviews and questionnaires. This learning media goes through the validation test stages of material experts as many as three experts, media expert validation tests as many as two experts, and product trials. The target of this product trial was students of class V as many as 20 students. Based on the results of the study, the media expert validation average was 47 in the very feasible category, the material expert validation was 45 in the very feasible category, and the user responses were 92.9% in the very good category. Thus, it could be concluded that animated cartoonvideos were suitable for use as learning media on the theme of objects around us in fifth-grade elementary school.